Eksplorasi Dimensi Public Speaking dalam Kepemimpinan Organisasi Mahasiswa - Suhari Muharam; Nelly Westari; Burhanuddin Burhanuddin (SAP (Susunan Artikel Pendidikan), 2026)
Leadership in student organizations requires a variety of competencies. Although the significance of public speaking in student organizations has been widely discussed, there remains a need for research that specifically examines the aspects of public speaking that make it a core skill. This study focuses on the aspects of public speaking as a core skill in student organization leadership. This study was conducted using a qualitative approach with a case study design at an Islamic university in Jakarta from May 2025 to December 2025. The researcher utilized NVivo 12 Pro software to visualize the coded data resulting from the analysis of collected interviews, observations, and documentation. Based on the analysis through the visualization of coded data using NVivo 12 Pro software, it is evident that public speaking plays a crucial role in fostering coordination, maintaining team cohesion, and organizational leadership. Other aspects, such as social and interpersonal aspects, psychological and self-control aspects, and technical aspects, further underscore the importance of public speaking skills in shaping effective and high-quality leadership within student organizations. These findings demonstrate that public speaking is not merely about the ability to speak in public but also encompasses social, psychological, and technical dimensions that play a vital role in building leadership effectiveness, strengthening organizational coordination, boosting self-confidence, and fostering harmonious interpersonal relationships within student organizations.